PERANCANGAN SISTEM INFORMASI BISNIS DI PERUSAHAAN MINUMAN UNTUK CAMPURAN JAMU - Albert Eko Pangaribowo (CALYPTRA, 2017)
Abstract – This company engaged in the manufacture of beverages which have a distribution in East Java, Central Java and Madura. Data processing is still done manually from the operational side, causing some of the problems which are admin or leader often miscalculated the amount of inventory, accounts receivable and payable, and the calculation of the amount of inventory, which slowly leads to lack of effectiveness of working time. So the purpose of this thesis is to analyze and make improvements job description in accordance with the improvement of information systems, conduct analysis and improvement of data flow diagrams and system procedures, and make the system database using Microsoft Access for help sorting, ease of processing, and data backup , this expected to reduce human error in calculations and also can facilitate leader and admin in searching data and decision-making will more accurately and quickly. It also can make it easier to monitor the activity of purchasing, sales, and inventory in the warehouse so expect an information system that will be applied will have a positive impact for the company. Keywords: Management Informastion System, Ms. Access, Flowchart